Mechanical Thrombectomy for the Treatment of Anterior Cerebral Artery Occlusion: A Systematic Review of the Literature - Dabhi, N.; Mastorakos, P.; Sokolowski, J.; Kellogg, R.T.; Park, M.S. (American Journal of Neuroradiology, 2022)
BACKGROUND: The overall safety and efficacy of mechanical thrombectomy for anterior cerebral artery strokes remain unclear.PURPOSE: Our aim was to summarize procedural and clinical outcomes in patients who underwent mechanical thrombectomy for treatment of anterior cerebral artery ischemic stroke.DATA SOURCES: A systematic literature review was performed using PubMed, Ovid MEDLINE, and the Web of Science from inception until March 4, 2022.STUDY SELECTION: We identified 9 studies with a total of 168 patients with mechanical thrombectomy–treated anterior cerebral artery occlusions.DATA ANALYSIS: Recanalization, procedural data, and clinical outcome at last follow-up were collected and summarized. Categoric variables were reported as proportions. The χ2 test of independence or the Kruskal-Wallis test was performed to assess the relationship between selected variables and the anterior cerebral artery embolus type (ie, primary isolated anterior cerebral artery, primary combined anterior cerebral artery, and secondary anterior cerebral artery occlusion) or the mechanical thrombectomy technique.DATA SYNTHESIS: For mechanical thrombectomy–treated anterior cerebral artery occlusions, recanalization modified TICI 2b/3 was achieved in 80%, postprocedural complications occurred in 17% of patients, and the 90-day mortality rate was 19%. The rate of symptomatic intracranial hemorrhage varied depending on the anterior cerebral artery embolus type (χ2 = 8.45, P = .01).LIMITATIONS: This analysis did not consider factors such as small-study effects that affect reliability and limit interpretation.CONCLUSIONS: Mechanical thrombectomy for the treatment of anterior cerebral artery occlusions is safe and efficacious, offering a favorable rate of recanalization and procedural complications. Mechanical thrombectomy–treated anterior cerebral artery occlusions appear to have lower rates of short-term good functional outcomes and an increased risk of symptomatic intracerebral hemorrhage compared with mechanical thrombectomy–treated MCA/ICA occlusions. Single and multicenter studies are needed to further examine the safety and efficacy of mechanical thrombectomy–treated anterior cerebral artery occlusions.ACAanterior cerebral arteryICHintracerebral hemorrhageMTmechanical thrombectomymTICImodified TICI